ANALYZING THE ECOLINGUISTICS FOR THE LANGUAGE OF THE KARAMAEE BOOK IN THE KURDISTAN REGION - Shabaz, Salah; Abdullah, Abdulsalam (Humanities Journal of University of Zakho, 2026)
In an era where environmental crises have become a global threat, this study, based on the framework of Ecolinguistics, provides an ecological analysis of the "environmental stories we live by" that are constructed in the "Karamee" (Competency) school textbook series in the Kurdistan Region. By analyzing three selected samples from the primary education stages (grades 2, 5, and 8) and using the analytical tools of Arran Stibbe (such as framing, erasure, and metaphor), the research concludes that the official educational discourse systematically narrates three main ideological stories. First, the powerful story of anthropocentrism, in which nature is represented as a resource for human benefit, and its independent and intrinsic value is reduced to mere utilitarian benefit. Second, the story of the passive citizen and the effective authority, a narrative that constructs an idealized image of state institutions as the sole problem-solvers while strategically erasing independent community action and the idea of self-reliance. Third, the story of simplified and depoliticized problems, where environmental issues are decontextualized from their complex political and economic contexts and presented as matters of individual morality or technical management, thereby concealing the role of corporate interests and systemic policies. In short, the research shows how environmental discourse, under the guise of education, is used to construct a specific worldview and produce the "good citizen" who is compliant with the existing system; a citizen who holds good attitudes but is equipped with limited critical skills to face real-world problems.